Stem cells and their role in pituitary tumorigenesis. (15th April 2017) - Carreno, Gabriela; Gonzalez-Meljem, Jose Mario; Haston, Scott; Martinez-Barbera, Juan Pedro
Abstract: The presence of adult pituitary stem cells (PSCs) has been described in murine systems by comprehensive cellular profiling and genetic lineage tracing experiments. PSCs are thought to maintain multipotent capacity throughout life and give rise to all hormone-producing cell lineages, playing a role in pituitary gland homeostasis. Additionally, PSCs have been proposed to play a role in pituitary tumorigenesis, in both adenomas and adamantinomatous craniopharyngiomas. In this manuscript, we discuss the different approaches used to demonstrate the presence of PSCs in the murine adult pituitary, from marker analyses to genetic tracing. In addition, we review the published literature suggesting the existence of tumor stem cells in mouse and human pituitary tumors. Finally, we discuss the potential role of PSCs in pituitary tumorigenesis in the context of current models of carcinogenesis and present evidence showing that in contrast to pituitary adenoma, which follows a classical cancer stem cell paradigm, a novel mechanism has been revealed for paracrine, non-cell autonomous tumor initiation in adamantinomatous craniopharyngioma, a benign but clinically aggressive pediatric tumor. Highlights: Studies in humans and mice suggest a role for pituitary stem cells in tumorigenesis. The cancer stem cell (CSC) model explains the origin of several tumors. Several CSC populations have been discovered in human pituitary adenomas. Evidence suggests pituitary adenoma pathogenesis follows the CSC model. Mouse models of craniopharyngioma reveal a role for paracrine tumorigenesis.